THE EVOLUTION OF ORGANIZATIONAL BEHAVIOR PARADIGM: A SYSTEMATIC REVIEW FROM CLASSICAL THEORY TO DIGITAL PRACTICE - Stanley Prabowo; Sunarto Budiono; Sopiah (RADJA PUBLIKA, 2025)
Digital transformation has radically changed how organizations operate and challenged the validity of classical theoretical approaches that have long dominated organizational studies. This article aims to examine the evolution of organizational behavior paradigms by tracing the contributions of classical theories, behavioral dynamics in digital environments, and the conceptual transition toward hybrid organizational models. The study employs a Systematic Literature Review (SLR) approach guided by PRISMA, analyzing 21 scholarly articles from reputable journals published in the last five years. The synthesis results indicate that classical theories remain relevant as a foundation for structural stability but must be integrated with principles of flexibility and digital learning to meet the needs of contemporary organizations. The hybrid conceptual model developed in this study represents a significant theoretical contribution in bridging the dichotomy between classical and digital approaches. Furthermore, this article proposes a future research agenda through cross-sectoral approaches and capability-based integration. The main contribution of this study lies in formulating a conceptual framework that reconciles structural efficiency with digital innovation in modern organizational behavior